Safety evaluation of Galdieria high-protein microalgal biomass. (21st November 2019) - Modeste, Virginie; Brient, Alizée; Thirion-Delalande, Catherine; Forster, Roy; Aguenou, Corinne; Griffiths, Hywel; Cagnac, Olivier
Protealg ® is the dried and ground whole biomass of Galdieria sulphuraria, a microalga naturally rich in protein and phycocyanin, and contains carotenoids. It is expected that Protealg will be consumed as a food ingredient or supplement by the general public. The safety of Protealg was evaluated in an Ames bacterial reverse mutation test, in vitro mammalian cell micronucleus test, and 13-week oral toxicity study in rats at the dose levels of 500, 2000, and 5000 mg/kg/day. The 13-week toxicity study included a 4-week treatment-free period to evaluate recovery. A functional observation battery and ophthalmology examinations were performed, and hematology, blood biochemistry, thyroid hormone, and urinalysis parameters were determined. Seminology parameters and estrus cycle staging were investigated. A macroscopic necropsy examination was performed and tissues were examined microscopically. Protealg showed no evidence of mutagenicity or clastogenic activity. It was well tolerated by rats and no clinical findings indicative of toxicity were observed. There were no significant findings in the in-life or post-mortem investigations. In conclusion, no toxicity was observed after administration of Protealg at dose levels up to 5000 mg/kg/day to rats for 13 weeks, supporting the safety of Protealg for use as a high protein food supplement. The NOAEL was established as 5000 mg/kg/day. Allowing for a margin of exposure of 100-fold, the corresponding anticipated daily intake will be 50 mg/kg/day equivalent to 3.5 g/day for a 70 kg subject. Incorporation levels in various foods will be defined on the basis of appropriate exposure estimations using official recommendations.